2019
DOI: 10.1164/rccm.201901-0094oc
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin during Acute Chronic Obstructive Pulmonary Disease Exacerbations Requiring Hospitalization (BACE). A Multicenter, Randomized, Double-Blind, Placebo-controlled Trial

Abstract: Augustinus-A Debrock (PI), P Ardies (Coordinator). Imelda ziekenhuis-T Lauwerier (PI), A Delbaere (Coordinator). UZ Brussel-W Vincken (PI), S Hanon (Co-I), D Schuermans, K Van Eeckhoudt (Coordinators). CHU St.-Pierre-V Ninane (PI), M Gabrovska (Co-I), F De Cock, S Carlier (Coordinators).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…28,29 The importance of this process is suggested by the link between the reduced phagocytic capacity of the AMs of patients with chronic obstructive pulmonary disease (COPD), and their failure to clear lung infections. 32 In mice, other phagocytic receptors, such as the macrophage receptor with collagenous structure (MARCO), are important for clearance of respiratory pathogens including Streptococcus pneumoniae and Mycobacterium tuberculosis. 32 In mice, other phagocytic receptors, such as the macrophage receptor with collagenous structure (MARCO), are important for clearance of respiratory pathogens including Streptococcus pneumoniae and Mycobacterium tuberculosis.…”
Section: Alveolar Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 The importance of this process is suggested by the link between the reduced phagocytic capacity of the AMs of patients with chronic obstructive pulmonary disease (COPD), and their failure to clear lung infections. 32 In mice, other phagocytic receptors, such as the macrophage receptor with collagenous structure (MARCO), are important for clearance of respiratory pathogens including Streptococcus pneumoniae and Mycobacterium tuberculosis. 32 In mice, other phagocytic receptors, such as the macrophage receptor with collagenous structure (MARCO), are important for clearance of respiratory pathogens including Streptococcus pneumoniae and Mycobacterium tuberculosis.…”
Section: Alveolar Macrophagesmentioning
confidence: 99%
“…30 This is associated with decreased expression of phagocytic molecules such as the mannose receptor, and may be restored by treatment with azithromycin, which increases the phagocytic capacity of AMs, 31 and may improve patient outcomes. 32 In mice, other phagocytic receptors, such as the macrophage receptor with collagenous structure (MARCO), are important for clearance of respiratory pathogens including Streptococcus pneumoniae and Mycobacterium tuberculosis. 33,34 In humans, MARCO polymorphisms that reduce phagocytic capacity in monocyte-derived macrophages are linked to tuberculosis susceptibility, 33 and lower MARCO expression on AMs from diabetic mice reduces their ability to phagocytose M. tuberculosis.…”
Section: Alveolar Macrophagesmentioning
confidence: 99%
“…83e86 More recently, a study showed that azithromycin therapy also may have a role during the highest risk period after acute exacerbation of COPD (AECOPD). 87 In the study by Vermeersch and colleagues, 87 301 patients were enrolled after an AECOPD and received 3 months of azithromycin or placebo. 87 Patients that received therapy had a lower rate of treatment failure after 3 months compared with placebo (49 vs 60%, HR ¼ 0.73; 95%CI 0.53-1.01, P ¼ .0526).…”
Section: Macrolidesmentioning
confidence: 99%
“…Antibiotic use is considered to be one of the most important perturbations for the airway microbiota. In recent years, macrolides have been widely used in infectious diseases and a range of chronic in ammatory airway disorders, including cystic brosis, bronchiectasis, chronic obstructive pulmonary disease and persistent uncontrolled asthma [10][11][12][13][14]. Previous randomized placebo-controlled trials have shown that, after exposure to long-term macrolide therapy, a signi cant reduction in the diversity of respiratory microbiota and Haemophilus in uenzae load can be observed in patients with lung diseases [15,16].…”
Section: Introductionmentioning
confidence: 99%